Shear mechanical properties and failure modes of rock with V-shaped intersecting double-cracks - Zhou, Zhiqiang; Zhao, Yu; Bi, Jing; Cheng, Hao; Wang, Chaolin (Theoretical and applied fracture mechanics, 2023)
•The physical and mechanical characteristics of red sandstone samples with two V-shaped intersecting cracks under direct shear condition are studied.•A virtual-bond method based SPH algorithm is developed and used to simulate the fracture process of V-shape cracked sandstone samples under direct shear condition.•The crack evolution mechanism of V-shape cracked rock under shear condition is systematically explained by SPH algorithm. Red sandstone samples with V-shaped intersecting double-cracks are used as the tested materials. The strength, failure and crack evolution of intersecting cracked rock samples under shear load are studied by laboratory tests and numerical simulation. A virtual-bond method based smoothed particle hydrodynamics (SPH) algorithm is developed and used to simulate the fracture of V-shape cracked sandstone samples under direct shear. It overcomes the disadvantages of traditional SPH algorithm for calculating discontinuous problems by introducing the particle damage coefficient. The results shows that intersecting crack distance and angle have an influence on peak stress, crack initiation stress, crack coalescence mode, and failure mode. The crack evolution and stress field interaction of V-shape cracked rock under shear is systematically explained by the SPH algorithm.